ANALISIS FEMINISME DWILOGI NOVEL SURGA YANG TAK DIRINDUKAN KARYA ASMA NADIA - Malinda Erda; Christanto Syam; Sesilia Seli (Universitas Tanjungpura, 2019)
Abstract The data of this study is the Dwilogi Surga Yang Tak Dirindukan by Asma Nadia. Data that was collected was analyzed by using a non-interactive analysis model with three steps, namely: (1) data reduction (2) data presentation (3) drawing conclusions or data verification. The results of this study are as follows (1) the role of femalecharacter as Ibu includes: as an educator, a nanny, supervisor an introducer to culture, a companion husbands, and as policy makers. Role as wife: as a housewife, and as a companion to husband. Role as worker: woman as writer, or an employee. (2) the role of woman in society: first, the character Ibu as a wife, a caregiver, and a supervisor of child development. Second: wife's attitude as the manager of the household, wife's attitude as husband's companion, wife's attitude as husband's companion, wife's attitude as a member of the community. (3) the image of a female figure named Arini is a strong, kind, gentle woman always fighting for the happiness of her children. The image of Mei Rose, an orphaned woman who lives with her aunt, her life is hard and she experience many things in her life that teach her how to be a strong and independent woman. Keywords: Analysis, Dwilogi, Feminism